Adoption of personal service robots in India. Issue 4 (December 2022) - Mukherjee, Jaydeep
Abstract: Adopting a new product depends on consumers' product perceptions, psychographics, and cultural contexts. This study combines stimulus-organism-response (S-O-R) and two-factor models to develop a comprehensive model for consumers' intention to adopt artificial intelligence-powered personal service robots. Data were collected from 400 consumers in India, using existing validated scales from the literature. Structural equation modelling and path analysis were used to test the model fit. Findings suggest that consumers' intention to adopt a personal service robot is based on perceived usefulness and risk, mediated by resistance bias. Contributions to the extant academic knowledge and marketing applications are discussed.